HUBUNGAN BUDAYA ORGANISASI, DUKUNGAN ORGANISASI DAN MOTIVASI KERJA DENGAN KINERJA KARYAWAN PERUSAHAAN DAERAH AIR MINUM TIRTANADI PROVINSI SUMATERA UTARA - Delviyandri Delviyandri; Azhar Aziz (Analitika: Jurnal Magister Psikologi UMA, 2010)
This study aims to look at the relationship of organizational culture and organizational support to employee motivation to work with the performance of the Regional Water Company Tirtanadi North Sumatra Province. In line with the existing theoretical basis, put forward a hypothesis:  There is a significant positive relationship to organizational culture, organizational support, employee motivation to work with the performance of PDAM Tirtanadi North Sumatra Province.In proving the above hypothesis, we used the regression method of data analysis three predictors. Based on data analysis of the results obtained:  There is a significant positive relationship to organizational culture, organizational support, motivation to work together with the performance of employees. This result is evidenced by the coefficient R = 0.371 with R.square = 0.138 where p <0.050. 2) As for the contribution of organizational culture variables on the performance of employees by 11.4%, for the variable of organizational support for employee performance based on analysis of data in this study was 9.1%, and for the motivation variables on the performance of employees by 1.06% . So that the total effective contribution of these three variables on the performance of employees by 13.81%. From the results it is known that there are still 86.1% influence of other factors on the performance of employees.            In general, the results of this study illustrate that employees have a very high organizational culture, organizational support is very high and has a very high motivation to work well, while the performance of acquired employees classified as very high as well.